PELAYANAN KASSA DENGAN PENDEKATAN ANALISIS SISTEM ANTRIAN PADA PT. CARREFOUR CITRA GARDEN MEDAN - Tamba, Darwis (Jurnal Manajemen dan Bisnis, 2012)
PT. Carrefour Citra Garden Medan engaged in the retail market various products, such as fresh, bazaar, textile, and grocery applane. The number of customers who shop from January to December 2010 fluctuates every month and long lines occurred in August when the feast of Eid al-Fitr and December when the Christmas and New Year's Eve. From the description, formulated the following research problem: "Why is the gap between the queuing system raises expectations with actual service time at the PT. Carrefour Citra Garden Field ".The research objective was to determine and analyze the queuing system on PT. Carrefour Citra Garden Medan. Benefits of the research is to provide information material to the company in the form of advice regarding the analysis of queuing systems. The study population is the number of customers of PT. Carrefour Citra Garden Field from 2009 until 2010. The samples taken months from January to December 2010. Required data are collected through observation and documentation techniques. Data analysis technique used is descriptive method. From the results of the discussion was concluded that the long queues at the PT. Carrefour Citra Garden Medan often occur on Saturday at 17.00 pm - 20.00 pm, and on a Sunday or holiday queues at 12.00 am - 14.00 pm and at 17.00 pm - 20.00 pm. Standard service time for each customer at the PT. Carrefour Citra Garden Medan maximum of 1 minute, yet customers have to wait up to 20 minutes at the feast of Eid al-Fitr and Christmas Day at 9 minutes. Customer arrival rate at PT. Carrefour Citra Garden Medan is not constant, the time required to serve every customer is different, Kassa served on a first come, first served basis and unlimited customer population. The probability of unemployed workers pads reach 4%. The number of customers in the queuing system at 43 people. The probability of the whole staff busy pads reach 94.91%. Customer in the queue system to 33 people. The time spent waiting and served customers to reach 26 minutes. Time spent waiting for customers to be served up to 20 minutes. This shows that the waiting time to be served is still too high. Suggestions are given for consideration to the management company is the best, firms pay more attention to the system queue by adding pads officers to serve customers at the time of school entry, the feast of Eid al-Fitr and Christmas celebrations and other holidays to reduce the long queues . To avoid the presence of officers who are unemployed pads, the company should provide to an officer other duties such as checking and making gauze packing.